Evaluation of Serum Uric Acid Levels in Essential Hypertensive Patients - A. M. Siddiqui, A. R. Shinde, Supriya Shete, H. N. Khan (International Journal of Innovative Research in Medical Science, 2016)
Elevated serum uric acid concentration has been reported to be associated with an increased risk of coronary heart disease and is commonly encountered with essential hypertension, including untreated hypertension and type 2 diabetes mellitus, which are in turn associated with coronary heart disease. Aim: To estimate serum uric acid levels in hypertensive patients and normal control by kit method on ERBA XL-640 Fully Automated Analyser. Material and Methods: This case control study was conducted at Dr.Shankarrao Chavan Government Medical College, Nanded. A total of 100 patients were studied of which 50 essential hypertensive patients were cases and 50 were controls who were patients without hypertension. Result: It was observed that the value of mean serum uric acid was 6.1mg% significantly more in cases than that was in control group 4.4%. This value rises with the duration and the severity of hypertension. It is evident in the form of 5.1mg% and 6.3mg% respectively in cases of stage1 and stage 2 hypertension and 4.6mg% and 6.9mg% in <5 years and >5 years after diagnosis of hypertension. Conclusion: Serum uric acid can be used as an biochemical marker to determine the severity and duration of hypertension.